Predictors for waiting time for coronary angioplasty in a high risk population. - Gaffney, B (1995)
Objective--To describe the clinical and non-clinical factors which influence the waiting time from initial angiography to angioplasty. Design--Follow up of a random sample of 106 patients undergoing their first coronary angiography for whom a decision to revascularise by percutaneous transluminal angioplasty was made in 1991. The period between the date of angiography and the date of angioplasty and various clinical characteristics of patients were retrieved from medical notes in mid 1993. Patients were sampled from those investigated in the two Northern Ireland catheterisation laboratories in Belfast, which provide services for the whole of the province (population 1.5 million). Main measures--The dependent variable was the period between initial angiography and angioplasty, and the independent variables included age, sex, distance from cardiac catheterisation centre, referral source, characteristics of the clinical history, severity of angina, and anatomical extent of disease. Cox's proportional hazards analysis was used to derive a relative hazard, expressing the relative chances of revascularisation occurring at any time during follow up. Results--Of the 106 patients studied, 93 had had percutaneous transluminal angioplasty at follow up. The most important predictors of waiting time were the presence of severe angina (relative hazards 3.1(95 % confidence interval (95% CI) 1.4-6.8) and 2.7(1.2-6.2) for Canadian Cardiovascular grades III and IV v angina grade I angina), a recent history of myocardial infarction (relative hazard, 2.5(1.3-4.8), and whether or not the patient was economically active (relative hazard 0.6(0.4-1.0) for economically inactive v active patients). Although there was also an association with the relative deprivation of the area of residence of the patient it had no clear linear trend. Conclusions--Although waiting time for percutaneous transluminal angioplasty was predictably related to the patient's clinical presentation, demographic factors may also be important in determining access to intervention. These factors clearly merit further study; ultimately, the evaluation of equity in a waiting time distribution may more properly be a societal rather than a clinical judgment.